(untitled) (Progressive Agriculture, 2020)
The wastewater reuse for the purpose of irrigation may have a significant contribution to reduce water pollution, maximize water utilization and restore nutrient content of soils. An experiment was conducted at Environmental Science Field Laboratory, Bangladesh Agricultural University, Mymensingh from January to May, 2015 to investigate the effects of wastewater irrigation on soil physico-chemical properties (Soil texture, pH, electrical conductivity (EC), organic matter (OM), nitrogen (N), phosphorous (P), potassium (K), sulphur (S) and sodium (Na)) as well as yield and yield contributing characteristics of tomato crop. In this study, irrigation water, e.g., normal water, domestic wastewater, municipal wastewater and industrial wastewater was used as treatment with three replications. Soil and fruits were collected for analysis during last harvest. From the result, it is found that most of the chemical properties; OM, EC, N, K, S and Na contents were higher in wastewater treated soil compared to normal water irrigation. Among the treatments, plant height, LAI and yield were also higher in wastewater treated plot compared to normal water irrigated plot. Cost benefit analysis indicated that municipal wastewater irrigation gave more profit due to higher yield compared to domestic and industrial wastewater irrigation. From the study, it could be concluded that municipal wastewater irrigation was more profitable in respect of soil nutrient content and yield of tomato. Progressive Agriculture 30 (4): 352-359, 2019